A multiomics approach reveals novel regulators of plasma factor V levels, highlighting CLEC4M as a clearance receptor: thrombosis and hemostasis - Munsch, Gaëlle; Mohapatra, Adarsh K.; van Hylckama Vlieg, Astrid; Kleber, Marcus E.; Martinez-Perez, Angel; Le, Ngoc-Quynh; Hindberg, Kristian Dalsbø; Dusart, Philip; Germain, Marine; Thibord, Florian; Deleuze, Jean-François; Delgado Gonzales de Kleber, Graciela; et al. (Blood, 2025)
Coagulation factor V (FV) is a key protein in maintaining the hemostatic balance, with abnormal plasma levels associated with both thrombotic and hemorrhagic conditions. We propose a comprehensive bioinformatic analysis integrating large-scale proteogenomics and transcriptomic data from original and public data sets. We identify a biological fingerprint of 26 new proteins and loci involved in the regulation of plasma FV levels. Furthermore, the messenger RNA expression levels of 10 of these components demonstrate strong correlation in the liver. In addition, we provide experimental evidence for the involvement of one of the newly identified players (CLEC4M) in the clearance of FV. This work opens new avenues for a better understanding of the physiological processes involved in thrombotic and bleeding disorders.
Online verfügbar: 15. Mai 2025, Artikelversion: 31. Juli 2025
Gesehen am 17.11.2025